Production of low-density particleboards from Ochroma pyramidale wood - Rios, Polliana D'Angelo; Buss, Rodrigo; Durigon Melo, Natalia; Hoffmann, Daniela; Seibet Kuhn, Leonardo; de Souza, Luana; Stange, Rafaela; Cunha, Alexsandro (Maderas. Ciencia y Tecnología, 2025)
Given the need to identify alternative wood species for the sustainable production of low-density particleboards, this study aimed to produce and evaluate low-density particleboard panels made from Ochroma pyramidale (balsa). Trees of Ochroma pyramidale (balsa) aged 6 and 10 years (three trees per age group) were harvested for this purpose. Homogeneous low-density panels were then fabricated using two different ages of Ochroma pyramidale (balsa) in combination with Pinus spp. as a control. The panels were produced with densities of 200 kg/m³; 300 kg/m³; 400 kg/m³ and 500 kg/m³, resulting in a total of 13 different treatments. During the pressing process, a temperature of 180 °C, a specific pressure of 30 kgf/cm², and a pressing time of 18 minutes were applied. Physical and mechanical properties were assessed on the panels after immersion in water for 2 hours and 24 hours. The physical tests revealed an increase in swelling as the panel density increased at both 2-hour and 24-hour intervals. Conversely, water absorption decreased as the density of the panels increased, for both immersion times. Mechanical testing, including modulus of rupture, modulus of elasticity, and perpendicular tensile strength, showed an increasing trend in values, indicating enhanced mechanical properties with higher panel density. Overall, Ochroma pyramidale (balsa) demonstrates significant potential as an alternative species to produce wood panels.